Alignment of regional tax revenue administration business process with standard operating procedures: A case study of East Surabaya Samsat - Nural Achmad Raainaa (Jurnalku, 2026)
To achieve optimal management of regional tax revenues, a structured administration process is required that complies with applicable regulations. Regional tax revenue administration encompasses a series of activities, from receipt, recording, and payment to reporting and accountability for tax revenues. The entire process must be implemented based on established Standard Operating Procedures (SOPs) to ensure uniformity in task execution, minimize administrative errors, and increase organizational effectiveness and efficiency. This study aims to analyze the compliance of regional tax revenue administration business processes with Standard Operating Procedures (SOPs) and identify remaining weaknesses in regional tax revenue management. The study employed a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that regional tax revenue administration business processes, including revenue administration, deposits, and reporting and accountability, have been implemented in accordance with applicable SOPs. However, several operational adjustments were identified in practice to address technical challenges without compromising the principles of accountability and transparency. Furthermore, the study identified several weaknesses, including suboptimal digitalization of administration and limited human resources in several operational functions. These findings indicate that the implementation of SOPs has supported the effectiveness of regional tax revenue management, but improvements are still needed through strengthening digital systems and optimizing human resources to enhance efficiency, transparency, and the quality of regional tax revenue governance.